DE-STIGMATIZING MENTAL HEALTH: EFFICACY OF A SCHOOL-BASED PSYCHOLOGICAL LITERACY INTERVENTION FOR PRIMARY SCHOOL STUDENTS - Pierre Dubois; Sophie lemoine; Marc Lefevre (Yayasan Adra Karima Hubbi, 2025)
Mental health issues among primary school students are often stigmatized, hindering their ability to seek help and develop coping strategies. Early intervention and psychological literacy programs in schools have been identified as key strategies in promoting mental well-being and de-stigmatizing mental health. This study aims to evaluate the efficacy of a school-based psychological literacy intervention designed to improve mental health awareness and reduce stigma among primary school students. The research involved a mixed-methods approach, with pre- and post-intervention assessments using both quantitative and qualitative data. A sample of 200 primary school students participated in the intervention, which included workshops, group discussions, and interactive activities focused on mental health awareness, coping skills, and reducing stigma. The results showed significant improvements in students’ understanding of mental health, their attitudes towards seeking help, and a reduction in stigma-related beliefs. Additionally, the intervention helped to foster an environment of empathy and support among students. The study concludes that school-based psychological literacy interventions are effective in promoting mental health awareness, reducing stigma, and fostering a supportive school environment. These findings highlight the importance of integrating mental health education into school curricula to support the psychological well-being of students.